2014
DOI: 10.2174/1874471007666140825121615
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Polyamidoamine (PAMAM) Dendrimers with Technetium-99m via Hydrazinonicotinamide (HYNIC)

Abstract: Dendrimers are branched nanomolecules, with a three dimensional structure, very low polydispersity and high functionality. Poly(amidoamine) (PAMAM) dendrimers are the most investigated class of dendrimers. In this study, PAMAM G4 dendrimer conjugated with HYNIC (hydrazinonicotinamide), an efficient bifunctional chelator, was characterized. Structure of the derivatized dendrimer was confirmed by (1)H-NMR and (13)C-NMR spectra and MALDI-TOF mass spectrometry. HYNIC-dendrimer was labeled with technetium-99m testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…These NPs demonstrated significant liver, spleen and kidney uptake. 70 , 71 Similar distribution values have been reported for antibody-conjugated G4 dendrimer targeted to tumour antigens, with increased tumour uptake. 72 In comparison, smaller G2 particles possess a faster excretion rate.…”
Section: Single Photon Emission Ct and Planar Scintigraphic Imaging Wsupporting
confidence: 69%
“…These NPs demonstrated significant liver, spleen and kidney uptake. 70 , 71 Similar distribution values have been reported for antibody-conjugated G4 dendrimer targeted to tumour antigens, with increased tumour uptake. 72 In comparison, smaller G2 particles possess a faster excretion rate.…”
Section: Single Photon Emission Ct and Planar Scintigraphic Imaging Wsupporting
confidence: 69%
“…However, radiolabeling of these conjugates as imaging probes has not been attempted so frequently. Recently, Kovacs et al (2014) have attempted to radiolabel PAMAM dendrimers with 99m Tc via hydrazinonicotinamide (HYNIC). These authors have reported the radiolabeling efficiency of 99.0% for 99m Tc–PAMAM–HYNIC conjugate and the preparation remained stable for up to 24-h.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our goal was to develop an imaging agent that selectively targets TAMs that express MRC1. For this purpose, we used PAMAM G5 dendrimers, a class of macromolecules synthetic, highly branched, and monodisperse with well-defined size and shape [24,25]. They are formed of a multi-carbon ethylene diamine core and abundant numbers of the primary amino group on the surface, which allows doing a range of chemical modification to obtain specific biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…They are formed of a multi-carbon ethylene diamine core and abundant numbers of the primary amino group on the surface, which allows doing a range of chemical modification to obtain specific biological properties. They are classified by generation number that is the number of focal points when going from the core towards the dendrimer surface [24]. PAMAM dendrimers have been widely used in biomedical applications in diagnosis and therapy [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%